Pendampingan Belajar Speaking bagi Anak di Oemah Ngaji, desa Argosari, Turi, Sleman, Yogyakarta - Ika Sulis Setianingsih; Tri Cahyaningrum; Julise Vertagina (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Speaking skills, especially English, are important for all people, especially children, as a support for various aspects of future life. In teaching language, one of the factors supporting the success of teaching English to children is the use of media, namely songs. The purpose of this service is to provide speaking learning assistance to children at Oemah Ngaji, Argosari village, Turi, Sleman. This service is carried out by providing learning assistance to grade 3-5 elementary school students who are also Oemah Ngaji students through the media of songs broadcast in video form, followed by learning assistance using worksheets, and evaluation using simple games. The result of this activity is that children enthusiastically participate in mentoring activities and looked very comfortable during material activities or discussions. Enthusiasm in participating in mentoring activities is very important to increase motivation to learn speaking further.